2019
DOI: 10.1002/pchj.311
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of the relationship between empathy and executive function

Abstract: The current meta‐analysis was designed to determine the relationship between executive function (EF) and empathy, as well as to identify any moderators. A search of Chinese and English databases yielded 18 studies and 67 effect sizes involving a total of 6006 participants. Results with the random effects model showed that EF was significantly positively correlated with empathy (r = .14, p < .001). Subgroup analysis showed that EF was more strongly related to cognitive empathy (r = .20, p < .001) than to affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 64 publications
5
49
1
1
Order By: Relevance
“…Thus, our results support previous findings suggesting Cognitive empathy, and in particular PT, is related to a wide array of executive function skills such as working memory, inhibitory control and cognitive flexibility (Aliakbari et al, 2013;Healey & Grossman, 2018;Yan et al, 2020).…”
Section: Shared Temporal Variability Between Iri Personal Distress Ansupporting
confidence: 91%
“…Thus, our results support previous findings suggesting Cognitive empathy, and in particular PT, is related to a wide array of executive function skills such as working memory, inhibitory control and cognitive flexibility (Aliakbari et al, 2013;Healey & Grossman, 2018;Yan et al, 2020).…”
Section: Shared Temporal Variability Between Iri Personal Distress Ansupporting
confidence: 91%
“…A recent meta-analysis [29] summarized these results, corroborating the evidence that empathy is strongly related to EF, and interestingly its cognitive facet is more closely related to executive skills than the affective one. Particularly, strong relationships were found between cognitive empathy and specific subcomponents of EF, including Inhibitory Control, Working Memory and Cognitive Flexibility, while affective empathy would only correlate to Inhibitory Control.…”
Section: Introductionmentioning
confidence: 56%
“…The principal goal of the present study was to assess the reciprocal relationship between empathic attitudes and EF in ADHD patients. A recent meta-analysis [29], mainly including studies performed on healthy subjects, found positive correlations between empathic competences and EF. Gökçen et al [43,44] reported similar findings in individuals with ASD traits, suggesting the role of EF in regulating empathic competences in neurodevelopmental disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations